The Alkylation of Enolates and Enol Derivatives: The Use of Silyl Enol Ethers - Ian Fleming (CHIMIA)
Specific metal enolates are not always alkylated regioselectively, not is there always complete control over the degree of alkylation. These difficulties and others can sometimes be overcome using enol derivatives, of which silyl enol ethers are particularly effective. Dienolates are generally alkylated in the α-position, but their silylated analogues show some aptitude for γ-alkylation.